2010
DOI: 10.1063/1.3478235
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation effects on paramagnetic defects in low-κ dielectrics for ultralarge scale integrated circuit interconnects

Abstract: The electronic properties of low-κ interlayer dielectric and etch stop layers are important issues in ultralarge scale integrated circuits development. Leakage currents are critical problems that are not well understood. A topic of current interest is ultraviolet curing of these films. We report on electron spin resonance and electrical measurements of low-κ films with and without ultraviolet exposure. This work provides fundamental understanding of the deep level defects likely involved in leakage currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Increasing defect densities and leakage currents after UV light irradiation are also discussed in other literature reports. 42 Sinha et al 43 suggested that photon irradiation produces trapped charges inside the low-k material, where such charge accumulation leads to potential reliability problems.…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…Increasing defect densities and leakage currents after UV light irradiation are also discussed in other literature reports. 42 Sinha et al 43 suggested that photon irradiation produces trapped charges inside the low-k material, where such charge accumulation leads to potential reliability problems.…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…[244][245][246] Additional studies have shown that UV curing can also result in an increase in paramagnetic defect densities and leakage currents. 247 Integrated requirements.-Cu/metal diffusion resistance.-An obvious integrated requirement for any dielectric diffusion barrier / metal capping layer is to prevent diffusion of the metal wire into the surrounding ILD. The presence of metal contamination in the ILD has been attributed to a number of reliability issues 248 such as increased leakage currents, [249][250][251] decreased TDDB lifetime [252][253][254][255][256][257][258] and shifts in CMOS device performance.…”
Section: -122mentioning
confidence: 99%
“…3 It has been shown that the defect bonding structures in the dielectric layers, as well as potential copper contamination due to the structure of the interconnects, are responsible for these large leakage currents. [4][5][6][7] It was found that defects in the dielectric layers lead to intrinsic leakage currents without the presence of metal layers. 5 Hence, an investigation of the nature of the defects in SiCOH along with methods to reduce them is critical for industrial application of these materials.…”
mentioning
confidence: 99%
“…[4][5][6][7] It was found that defects in the dielectric layers lead to intrinsic leakage currents without the presence of metal layers. 5 Hence, an investigation of the nature of the defects in SiCOH along with methods to reduce them is critical for industrial application of these materials. 8 For high-k dielectrics, specific processing steps were undertaken to exclusively modify each bonding structure of concern so that the resulting changes in defect concentration, as measured by electron spin resonance ͑ESR͒, can be directly linked to changes to specific chemical bonds.…”
mentioning
confidence: 99%
See 1 more Smart Citation